EMPOWERMENT OF COCOA FARMERS (THEOBROMA CACAO L.) DURING PRE AND POST-HARVEST IN EFFORT OF QUALITY IMPROVEMENT OF COCOA COMMODITY IN KOLAKA - Yolanda Fitria Syahri; H. Hastuti (Agrotech Journal, 2017)
Kolaka is known as "Kolaka Cocoa City". Cocoa is the main commodity of Kolaka Regency. Kolaka is one of the cities in Southeast Sulawesi. Southeast Sulawesi is one of the provisions in Sulawesi which is the center of cocoa production after South Sulawesi with total area of 260,458 ha and with production 142,156 tons (Ditjenbun, 2012). Cocoa production centers in southeast sulawesi are located in Latambaga and Samaturu Sub-districts. Partners in the IbM program are cocoa farmers of Induha Urban Village, Latambaga Sub-district and cocoa farmer in Samaturu Sub-district. Various cooperation programs have been conducted to improve the quality of cocoa commodities in Kolaka District. In its development, classical problems remain faced by partner farmers both in terms of production and business management. In terms of production, pre-harvest problems faced by farmers are cocoa pests and diseases, which cause the farmers’ dependence on pesticides and chemical fungicides as well as the age of plants, therefore, it is important to reduce the use of pesticides and chemical fungicides because in the long term it can have adverse impact on environmental sustainability and health. The problem of post-harvest for partner farmers is a low quality of cocoa production. Most cocoa farmers process cocoa fruits to be dried beans in a rough way so that ± 90% of the cocoa beans produced by farmers have a low quality with the main characteristic is not fermented. The problem faced by farmers  in the marketing chain is the oligopsoni market structure, where farmers are at the lowest position so that farmers do not have bargaining position. The objectives of IbM program were to 1) Reduce farmers’ dependence on pesticides and chemical fungicides with the utilization of environmentally friendly pesticides 2) Design the fermentor to improve the quality of cocoa beans 3) Enhance the bargaining position of farmers through the active role of Farmer group (Gapoktan)  in the marketing chain of cocoa